Research and Realization of Hierarchical Information Interaction in Multi-load Regulation System. Issue 1 (1st February 2023) - Zhang, Liuliu; He, Minyi; Xie, Wei; He, Zhen; Tan, Zhijun
Abstract: In the context of advancing the integration of power source network load storage and multi-energy complementary development, it is necessary to optimize the integration of power source, grid side, and load side resources to build a new power system with a high degree of integration of source network load and storage. The article analyzes the adjustable load distribution. In the scenario of multi-layer collaborative control, access methods are divided around load resource types and response characteristics, and an information interaction technology oriented to multiple load adjustments is proposed to achieve flexible and friendly interaction with various load aggregator systems. At present, research results have been obtained in the project. In practical applications, the flexible and friendly interaction of adjustable load resources enhances the flexible adjustment capability of the power grid and expands the space of adjustable load resources.